A sinister Vibrio fluvialis bacteremia in an elderly gentleman - Ahmad Tajudin, Edahayati; Ismail, Nabilah; Faisal, Ummu Salamah; Zainulabid, Ummu Afeera (2023)
Vibrio sp. causes gastroenteritis, wound infection, and bacteremia in humans after exposure to seawater or contaminated seafood. Human infections caused by V. fluvialis are mostly gastroenteritis. Here, we described a sinister case of V. fluvialis bacteremia in an elderly gentleman.